2010
DOI: 10.1097/bpo.0b013e3181f9fc03
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surgical Delay on the Outcome of Pediatric Supracondylar Humeral Fractures

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 31 publications
5
35
0
6
Order By: Relevance
“…In addition, we used a previously described system to measure the outcome of the procedures. 11 In this system, a ROM of at least 85% of the normal, contralateral side is considered satisfactory. Therefore, a patient with up to 20 degrees of loss of elbow motion would still be deemed satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we used a previously described system to measure the outcome of the procedures. 11 In this system, a ROM of at least 85% of the normal, contralateral side is considered satisfactory. Therefore, a patient with up to 20 degrees of loss of elbow motion would still be deemed satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were compared in the 2 study groups: need for open reduction, quality of fracture reduction, length of surgery, presence of neurological complications or vascular complications, pintract infection, loss of fixation, final carrying angle, ROM, and outcome. As describe in a previous study, 11 the outcome of the procedure was classified as follows: a satisfactory outcome was one in which there was a change in carrying angle of <10 degrees, 12 a ROM of at least 85% of the normal, contralateral side at the latest follow-up, and had no evidence of complications (neurological, vascular, or otherwise), loss of fixation, infection, or avascular necrosis (AVN) of the trochlea. For the purpose of this analysis, a pin-site granuloma was considered as an infection.…”
Section: Methodsmentioning
confidence: 99%
“…The most common fracture operatively treated at this institution is the supracondylar humerus fracture. To date several studies have been published on the outcomes of these fractures after surgical delay [12][13][14][15][16] . All of the studies reviewed found no increase in the complication rate, which has further allowed surgeons to address these injuries in a more delayed fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Die Sensibilitätsstörungen verschwanden jeweils innerhalb von 6 Wochen nach der geplant nach 4 bzw. 6 Monaten erfolgten Metallentfernung, im Rahmen derer der R. superficialis freigelegt und unverletzt vorgefunden wurde. In 7 Fällen (5,8 %) trat der Nervenschaden im Rahmen der Explantation auf.…”
Section: Radialisschaden Und Akute Frakturversorgungunclassified
“…Ein typisches Beispiel ist die Läsion des N. ulnaris auf Höhe des Sulcus ulnaris bei der K-Draht-Osteosynthese suprakondylärer Oberarmfrakturen, deren Rate mit bis zu 11 % angegeben wird [2][3][4][5]. Ein Großteil der Literatur zum Thema Inzidenz, Vermeidung und Behandlung von iatrogenen Nervenschäden nach Frakturbehandlung im Wachstumsalter beschäftigt sich dementsprechend mit dem N. ulnaris [6][7][8][9][10][11][12].…”
unclassified